Thermopuncture for the Diagnosis, Monitoring, and Treatment of Patients with Type 2 Diabetes - Valery Muzhikov; Elena Vershinina; Ruslan Muzhikov; Kirill Nikitin (Medical Association of Pharmacopuncture Institute, 2018)
Background: Type 2 diabetes (T2D) is a socially significant disease that affects millions of patients. There were an estimated 366 million people with this disease in 2011, and, according to the forecast, approximately 552 million will be affected by this disease in 2030. It is well known that the primary diagnosis and treatment of a patient with this disease are quite expensive. What should be done to make it possible for a patient to monitor his own state and provide treatment in his own home using telemedicine?To solve this problem, an alternative concept for the diagnosis, monitoring, and treatment at the basis of traditional Chinese medicine combined with mathematical methods of data processing has been used. Methods/Design: To assess the pattern thresholds of acupuncture channels of heat sensitivity in patients with T2D, the Akabane test was performed on 160 men and 243 women (total 696 tests), including the dynamics of surveillance. For comparison, a group of healthy individuals comprising 116 men and 277 women also participated. Results: It was found that the main difference between patients with T2D and the healthy individuals is the presence of a pronounced asymmetry between the right and left branches of the canals, primarily in the digestive system. At the same time, the level of asymmetry increases with the increase in the glycemic level. This dependence allows for the early diagnosis of T2D. Moreover, a targeted stimulation of the definite channels with a high level of asymmetry based on the individual calculations can decrease the glycemic level. Conclusion: The combination of the Akabane test with the use of mathematical analysis in patients with T2D makes it possible to trace the entire chain of carbohydrate metabolism at an individual level and to identify the compensatory mechanisms for more effective treatment of reflexotherapy methods. This kind of treatment and monitoring can also be performed by the patient independently in his own home. Keywords: Akabane test, hyperglycemia and hypoglycemia, telemedicine, type 2 diabetes